Um estudo sobre as equações de agregação em espaços de Morrey, Besov-Morrey e Fourier-Besov-Morrey - Pignatari, Marta Luiza Suleiman [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Neste trabalho, apresentamos condições para obter boa colocação global no tempo para uma classe de equações de transporte viscoso não-linear descrevendo fenômenos de agregação em biologia com dados iniciais em espaços de Morrey, Besov-Morrey e Fourier- Besov-Morrey. Estudamos também auto-similaridade e estabilidade assintótica em grandes tempos.

In this work we present conditions to obtain global-in-time well-posedness to a class of nonlinear viscous transport equations describing aggregation phenomena in biology with initial data in Morrey, Besov-Morrey and Fourier-Besov-Morrey spaces. We also study the self-similarity and asymptotic stability of solutions at large times.
A study of aggregation equations in Morrey, Besov-Morrey and Fourier-Besov-Morrey spaces
Keywords: Equações de transporte viscoso não linear; Quimiotaxia; Espaços de Morrey; Espaços de Besov-Morrey; Espaços de Fourier-Besov-Morrey; Comportamento assintótico; Nonlinear viscous transport equations; Chemotaxis; Morrey spaces; Besov-Morrey spaces; Fourier-Besov-Morrey spaces; Asymptotic behavior